PENERAPAN MODEL PEMBELAJARAN MAKE A MATH UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWAA PADA MATA PELAJARAN MATEMATIKA - Prihastini Oktasari Putri (Intersections, 2020)
This study aims to determine whether applying the Make A Math cooperative learning model can increase student learning activeness in mathematics. The type of research used is Classroom Action Research (PTK). This Classroom Action Research was carried out in two cycles, each of which included planning, action, observation and reflection. The sample in this study were all class VIIA students of SMP Negeri 7 Kebumen in the academic year 2018/2019, totaling 24 students. The instruments used in this study were observation, documentation and questionnaires.Based on the results of the study, it was concluded that the application of the Make a math type of cooperative learning model can increase student learning activeness in mathematics class VII SMP Negeri 7 Kebumen. The increase in student learning activeness can be seen in the questionnaire. Based on the questionnaire of student learning activeness using the Make A Type cooperative learning model, there was an increase from pre-cycle by 56.71% in the low category, increasing in the first cycle to 67.03% in the moderate category and increasing again in the second cycle, namely by 81.04%